Uma cidade em transformação: a influência da atividade do crediário nas mudanças da paisagem urbana de Tenente Ananias-RN - Souza, Marcelo Luis de Amorim (2014)
Studies on the urban landscape and on the changes of the urban space are relevant, since they reveal the economic dynamics and the way of life in the cities. Research on small towns, in particular, can display particular aspects and by so doing broaden the comprehension of this theme. The purpose of this research is to analyze the changes in the urban landscape and in the way of life of the inhabitants of the town of Tenente Ananias-RN that have been taking place since the 1990s up to the present (2013) and which result mainly from the commercial activity of crediário. The study is, therefore, a reflection on the impact of crediário economy on the urban landscape and on the way of life of a small town located in the hinterland of the State of Rio Grande do Norte. For this reason, it was necessary to study the landscape and the way of life found in Tenente Ananias in two moments: a) before the rise of the crediário, a period of time ranging from the town‟s initial emergence until the beginning of the 1990s; b) during the progress of crediário activity, from the beginning of the 1990s, when it starts, up to the present (2013). For this research, primary data (interviews, local survey visits) and secondary data (books, articles, reports, census data) were used. As a result of this study, it was possible to conclude that crediário plays a fundamental role for the explanation of the changes taking place in Tenente Ananias-RN, especially in the urban landscape and in the way of life of people. We have attempted, through this research, to contribute to the studies of a historical, social and economic process related to the urban landscape and space of a small town in the State of Rio Grande do Norte